Village Financial Performance Analysis Based on Effectiveness, Efficiency, and Growth Ratios in Tebing Batu Village, Sambas Regency - Tripan Huda Andika; Fuad Ramdhan Ryanto (PT. Maju Malaqbi Makkarana, 2026)
This study aims to analyze village financial performance based on effectiveness, efficiency, and growth ratios in Tebing Batu Village, Sambas Regency, during the 2019–2023 period. This study employed a quantitative descriptive method using secondary data obtained through documentation, including village revenue targets, revenue realization, expenditure budgets, expenditure realization, and financing budget data. The data were analyzed using effectiveness, efficiency, and growth ratio calculations to assess the achievement of revenue targets, the control of village expenditure, and the development of village financial performance over time. The results show that the effectiveness ratio was 60.71% in 2019, categorized as less effective, but improved to 100.25% in 2020 and 100.02% in 2022, both categorized as very effective. In 2021 and 2023, the effectiveness ratios were 99.99% and 99.74%, respectively, categorized as effective. The efficiency ratio remained in the very efficient category throughout 2019–2023, with values ranging from 39.14% to 51.16%. Meanwhile, revenue growth fluctuated, increasing by 57.86% in 2020, declining in 2021 and 2022, and rising again by 1.71% in 2023. These findings imply that Tebing Batu Village needs to maintain budget efficiency while strengthening revenue planning to achieve more stable financial growth.